Influence of an enhanced recovery programme on clinical outcomes and health-related quality of life after pancreaticoduodenectomy ad modum Whipple – an explorative and comparative single-centre study - Thomas Andersson; My Engström; Johanna Wennerblom; Hanna Gyllensten; Kristofer Bjerså (BMC Surgery)
Abstract Background The introduction of enhanced recovery programmes (ERP) in pancreatic surgery has significantly improved clinical outcomes by decreasing the length of hospital stay, cost and complications without increasing readmissions and reoperations. To complement evidence on these outcomes, there is a need to explore patients’ perspectives of a structured ERP. Therefore, this study aimed to explore the health-related quality of life (HRQoL) of patients before and after implementing ERP in pancreaticoduodenectomy ad modum Whipple (PD) at a regional surgical centre. Method This was an explorative and comparative single-centre study in Sweden. A prospective cohort receiving ERP was included between October 2019 and December 2022 (n = 73) and was compared with a retrospective pre-ERP cohort between October 2011 and December 2013 (n = 65). EQ-5D, the European Organization for Research and Treatment of Cancer (EORCT) Quality of Life Questionnaire Cancer 30 items (QOL-C30), and EORCT Quality of Life Questionnaire pancreatic cancer module (QOL-PAN26) were collected preoperatively and at three and six months postoperatively. Demographic and clinical variables were collected from patient charts. Complications were expressed using the Clavien-Dindo Classification and the Comprehensive Complications Index (CCI). Results There were no significant differences in general health, cancer- or disease-specific HRQoL between the pre-ERP and ERP cohorts. Length of stay was significantly shorter in the ERP cohort (16 vs. 11 days; p < 0.001). There was no significant difference in CCI. Conclusion No significant differences were found in the HRQoL of patients who participated in an ERP compared to those who did not. However, a significant decrease in LoS was found when ERP was applied. Trial registration Not applicable.